Client/Server Technology and its Impact on Enterprise Resource Planning System - Indra Cahyadi (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
In this Information era, Client/Server model is gaining popularity as people begin to reckon the benefits of this technology. As a method for dividing the tasks of the application into several dissimilar components in a networked system, this technology is bringing long term cost benefit for support and development.This paper serves the purpose of reviewing and discussing the client/server models. A comparison between ERP solution from Oracle and SAP, and a discussion of Service Oriented Architecture (SOA) impact on ERP and distributed system are also presented towards the end of this paper.Keywords: Client/Server Technology, ERP System, Service Oriented Architecture.